Model Explicit Intruction Dalam Meningkatkan Keterampilan Vokasional Pembuatan Taoge Bagi Anak Dengan Hambatan Kecerdasan - Nurliyana Kamzy; Armaini Armaini (PAKAR Pendidikan, 2019)
This study discusses vocational skills in making sprouts in mentally retarded children. This research is experimental research. The purpose of this study is to prove that an effective explicit intruction model is used to improve vocational skills in making sprouts in mildly mentally retarded children. The type of research used is the experimental method in the form of pre-experimental with the type of one group pretest-posttest design and compared using the Wilcoxon Rank Tast test. From the results of the research data, the average at the pretest was 53.80 while for the posttest there was an increase of 85.80. The data was processed more scientifically using the Wilcoxon test obtained by rank tast value between pretest and posttest 2,060 with Asymp. Sig (2-tailed) 0.039. The predetermined probability is α = 0.05. The alternative hypothesis is accepted because the probability <of a predetermined probability is 0.039 <0.05. So it is evident that the use of explicit intruction models in improving vocational skills in making sprouts in mentally retarded children increases.